Enterprise research and development activity in Poland in com-parison to eurozone countries - Magdalena Gostkowska-Drzewicka; Ewa Majerowska (Ekonomika, 2020)
During the years 2000-2018, the number of enterprises conducting research and development activity in Poland was increasing systematically, thus the expenditures on research and development were increasing as well. The impact of R&D activity on the level of innovation of both enterprises and entire economies is related to objective and subjective structure of these expenditures which means that is not connected only with the value of the expenditures for its financing. The purpose of this paper is to present the level of expenditures on R&D in the business enterprise sector in Poland, in comparison to Eurozone countries and to analyze the convergence of value of these expenditures in Poland. The authors of the article used description and analysis of the statistical data obtained from the EUROSTAT and the GUS (General Statistical Office in Poland) statistics and estimation of econometric models and testing the occurrence of sigma and beta convergence. Based on the results we state that the key issue is to further activate Polish enterprises within the sphere of research and development, because Poland, in comparison with Eurozone countries, ranks within the group of countries with low expenditures on research and development and with structures characteristic of less prosperous economies. The study allowed determination of occurrence of sigma and beta convergence in Poland, in comparison with the Eurozone countries.
Keywords: 330; R&D; expenditures on research and development; the business enterprise sector; innovation; beta and sigma convergence